Development and Validation of an Effective CRISPR/Cas9 Vector for Efficiently Isolating Positive Transformants and Transgene-Free Mutants in a Wide Range of Plant Species - Tang, Ting; Yu, Xiwen; Yang, Hong; Gao, Qi; Ji, Hongtao; Wang, Yanxu; Yan, Guanbo; Peng, Yan; Luo, Huifeng; Liu, Kede; Li, Xia; Ma, Chaozhi; et al. (Frontiers in Plant Science, 2018)
The CRISPR/Cas9 technique is a highly valuable tool in creating new materials for both basic and applied researches. Previously, we succeeded in effectively generating mutations in Brassica napus using an available CRISPR/Cas9 vector pKSE401, while isolation of Cas9-free mutants is laborious and inefficient. Here, we inserted a fluorescence tag (sGFP) driven by the constitutive 35S promoter into pKSE401 to facilitate a visual screen of mutants. This modified vector was named pKSE401G and tested in several dicot plant species, including Arabidopsis, Brassica napus, Fragaria vesca (strawberry), and Glycine max (soybean). Consequently, GFP-positive plants were readily identified through fluorescence screening in all of these species. Among these GFP-positive plants, the average mutation frequency ranged from 20.4% to 52.5% in Arabidopsis and B. napus with stable transformation, and was 90.0% in strawberry and 75.0% in soybean with transient transformation, indicating that the editing efficiency resembles that of the original vector. Moreover, transgene-free mutants were sufficiently identified in Arabidopsis in the T2 generation and B. napus in the T1 generation based on the absence of GFP fluorescence, and these mutants were stably transmissible to next generation without newly induced mutations. Collectively, pKSE401G provides us an effective tool to readily identify positive primary transformants and transgene-free mutants in later generations in a wide range of dicot plant species.